Fiqih Economic in Virtual Currency Implementation - Effendi, Kharisya Ayu; Latif, Sahraman D Hadji (IKONOMIKA, 2023)
Digital transactions are becoming very popular in the Islamic economic and financial industry. Therefore, it is very important to understand the provisions of economic fiqh so that Sharia principles are always actual and relevant to business changes and the demands of the times. This study aims to investigate fiqh in economic transactions using blockchain and metaverse technology. More in-depth research uses a case study design using qualitative methods that focus on implementing smart contracts and virtual currency in terms of economic fiqh studies. The findings reveal that the use of smart contracts and virtual currency is found to be able to replace the role of intermediaries in economic transactions. Thus eliminating the risk of fraud and cheating. Smart contracts can help ensure compliance with sharia and the use of virtual currency has an impact on economic fiqh, especially related to the legitimacy and halal use of the virtual currency itself. The expected implication is that to minimize risks and maximize benefits for the benefit of the people, the use of blockchain and metaverse technology in economic transactions requires further research and development efforts, as well as increasing public understanding of this technology from the perspective of economic fiqh.